Prevalence of Delayed Neuropathy and Intermediate Syndrome in Acute Organophosphorus Poisoning: A Cross-sectional Toxicological/Clinical Study - Rahimi, Mitra; Kefayati, Rezvan; Shadnia, Shahin; Erfan Talab Evini, Peyman (International Journal of Medical Toxicology and Forensic Medicine, 2022)
Background: Organophosphates are among the most common causes of poisoning worldwide—responsible for 3 million poisoning and 200000 deaths every year. Nearly 15% of people who are poisoned die. This cross-sectional toxicological/clinical study aimed to investigate the prevalence and influential factors in the incidence of delayed peripheral neuropathy and intermediate syndrome in acute poisoning with organophosphorus toxins. The study was conducted in Loghman Hakim Hospital, Tehran City, Iran, from 2017 to 2020. Methods: The study data were obtained from the patients’ records during follow-up. Data included demographic information (age, sex, etc.), vital signs, muscarinic, nicotinic, and neurological symptoms at admission, atropine therapy status, and pralidoxime intake status. Post-discharge complications were obtained, and patients’ Electromyography (EMG) and Nerve Conduction Velocity (NCV) results were recorded and evaluated during hospitalization and follow-up. Statistical analysis was performed using SPSS software, version 22. Results: Of 63 studied patients, 61.9% were female. The Mean±SD age of the patients was 31.90±13.128 years. Male patients were significantly (P<0.010) older than female ones. The most common muscarinic symptoms were nausea and vomiting (73.2%), diarrhea (34.92%), and abdominal pain (33.33%). Regarding the nicotinic symptoms, sweating (30.16%) and fasciculation (19.05%) were the commonest. Neurological complications were less common; seizures were observed in 3 cases (4.76%) and coma in 2 cases (3.17%). Most patients (79.4%) received pralidoxime with atropine. The Mean±SD days of treatment with atropine and pralidoxime were 5.51±3.52 and 4.06±4.62 days, respectively. Only one death was recorded. The results of the initial EMG-NCV test on the second day of hospitalization showed abnormalities in 4 patients (6.3%), indicating the presence of the intermediate syndrome. Conclusion: The results of the EMG-NCV tests at our patients’ follow-up (30 days) showed no abnormalities. Hence no cases of delayed neuropathy were seen. During hospitalization, one patient had flaccid paralysis and showed significant impairment on the EMG-NCV test (P<0.01).